Auyero J., M.F. Berti (2015), In Harms’s Way, The Dynamics of Urban Violence, Priceton, NJ: Princeton University Press - Guillem, Rémi (PARTECIPAZIONE E CONFLITTO, 2018)
For Book Reviews abstract is not required